2017
DOI: 10.1002/pros.23314
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Grading Gleason Score 7 Prostatic Adenocarcinoma on Needle Biopsy: Influence of Percent Pattern 4 and Other Histological Factors

Abstract: When pattern 4 is scattered amongst pattern 3 as opposed to being discrete foci, there is less interobserver reproducibility in grading Gleason score 7 cancer, and in this setting pathologists should consider obtaining second opinions either internally within their group or externally. Prostate 77: 681-685, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…36 Targeted biopsies also outperformed standard biopsies in detection of overall positive cores, percentage area of cores positive for cancer, cancer length of positive cores, perineural invasion, and more anteriorly located PCas. [37][38][39][40][41][42] GP 4 quantity in GS 7 PCa is an important pathologic parameter that may also influence treatment decisions. In GS 7 PCa, GP 4 is associated with adverse histopathologic outcomes and an increased risk of biochemical failure in patients undergoing radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Targeted biopsies also outperformed standard biopsies in detection of overall positive cores, percentage area of cores positive for cancer, cancer length of positive cores, perineural invasion, and more anteriorly located PCas. [37][38][39][40][41][42] GP 4 quantity in GS 7 PCa is an important pathologic parameter that may also influence treatment decisions. In GS 7 PCa, GP 4 is associated with adverse histopathologic outcomes and an increased risk of biochemical failure in patients undergoing radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The quantity of GP 4 has been used in determining candidacy for active surveillance and for selection of different radiation therapy protocols. 42 In this study, we explored the possibility that MRI-targeted biopsy may detect GS 7 PCa with greater GP 4 quantity. We indeed found that the mean percentage of GP 4 detected by MRI-targeted biopsy was significantly higher than that detected by standard biopsy (31.0% versus 25.2%).…”
Section: Discussionmentioning
confidence: 99%
“…1 Distinction between some GP 3 and GP 4 glands can be challenging, particularly between small and tangentially sectioned GP 3 glands versus poorly formed GP 4 glands and between tight clusters of GP 3 glands versus fused GP 4 glands. [30][31][32] Interobserver studies have shown that pathologists usually have problems classifying poorly formed glands as GP 4, particularly when seen admixed with intervening GP 3 glands versus when seen as a discrete cluster of GP 4 glands. 31,32 Although a practical approach is to ensure that tangential sectioning is not the cause of glands that appear poorly formed, some authors have proposed that interobserver reproducibility may be improved in the interpretation of poorly formed glands as GP 4 when a minimum number (.5) of poorly formed glands are in a cluster and not intermixed with well-formed glands.…”
Section: Gp Definitions and Interpretationsmentioning
confidence: 99%
“…[30][31][32] Interobserver studies have shown that pathologists usually have problems classifying poorly formed glands as GP 4, particularly when seen admixed with intervening GP 3 glands versus when seen as a discrete cluster of GP 4 glands. 31,32 Although a practical approach is to ensure that tangential sectioning is not the cause of glands that appear poorly formed, some authors have proposed that interobserver reproducibility may be improved in the interpretation of poorly formed glands as GP 4 when a minimum number (.5) of poorly formed glands are in a cluster and not intermixed with well-formed glands. 31 This approach has limitations in applications while dealing with extremely small foci of cancer.…”
Section: Gp Definitions and Interpretationsmentioning
confidence: 99%
“…It has been documented that interobserver reproducibility for the recognition of Gleason pattern 4 in prostate needle biopsies is not high. In particular, the rate of the agreement between an expert genitourinary pathologist and general pathologists was lower in cases where pattern 4 was scattered among pattern 3 than in those with discrete tumor foci ( 26 ). In a recent study ( 27 ), interobserver reproducibility of percent Gleason pattern 4 in prostate needle biopsy was also assessed in a prospective manner.…”
Section: Accuracy Of Estimated Percent Gleason Patternmentioning
confidence: 99%